1995
DOI: 10.1165/ajrcmb.13.1.7598939
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy using adenovirus carrying the herpes simplex-thymidine kinase gene to treat in vivo models of human malignant mesothelioma and lung cancer.

Abstract: Previous studies have shown adenoviral transfer of the herpes simplex virus thymidine kinase (HSVtk) gene followed by the anti-viral drug ganciclovir (GCV) can be used to successfully treat established human mesothelioma tumors growing within the peritoneal cavities of severe combined immune deficient (SCID) mice. These findings raised a number of questions important to the applicability, efficiency, and safety of this treatment strategy. In this report, we have further characterized the use of recombinant ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…This contrasts with other methodology, eg in vivo injection of genes using adenovirus, in which viral dissemination is revealed using RT-PCR. 30 These results further characterize the use of HVJ-AVE-liposome ex vivo transfer into transplant organs and suggest that clinical trials using this approach may be feasible.…”
Section: Figure 4 Representative Results Of Rt-pcr Showing Hvj F Protmentioning
confidence: 66%
“…This contrasts with other methodology, eg in vivo injection of genes using adenovirus, in which viral dissemination is revealed using RT-PCR. 30 These results further characterize the use of HVJ-AVE-liposome ex vivo transfer into transplant organs and suggest that clinical trials using this approach may be feasible.…”
Section: Figure 4 Representative Results Of Rt-pcr Showing Hvj F Protmentioning
confidence: 66%
“…These results are similar to our previous studies of mesothelioma and lung cancer. 27 Delivery of Ad.wt.tk led to a slightly different type of survival profile. In these animals, there was evidence of some early toxicity (at about 1 week after viral injection), but surviving animals had an increase in survival (median survival 52 days) with some animals living to 95-105 days.…”
Section: Figure 6 Kaplan-meier Survival Analysis Of Scid Mice With Esmentioning
confidence: 99%
“…8,9 Accordingly, adenoviral vectors encoding HSVtk (Ad.HSVtk) in combination with GCV have been used in several pre-clinical and clinical suicide gene studies directed against a variety of cancers including brain tumors, 10 head and neck tumors, 11 melanoma, 12,13 ovarian cancer, [14][15][16] and malignant mesothelioma. [17][18][19][20][21] Many of these animal studies have shown some therapeutic effects; however, one of the major shortcomings of adenoviral gene therapy has been the relatively low efficiency of recombinant gene transfer to target tumor tissues in vivo, thus, significantly limiting treatment efficacy. This occurs despite the presence of a 'bystander effect' where transfection of only a small percentage of malignant tumor cells is sufficient to achieve near complete tumor eradication in some animal studies.…”
Section: Introductionmentioning
confidence: 99%